2014
DOI: 10.1159/000359968
|View full text |Cite
|
Sign up to set email alerts
|

Competing Risks Model in Screening for Preeclampsia by Serum Placental Growth Factor and Soluble fms-Like Tyrosine Kinase-1 at 30-33 Weeks' Gestation

Abstract: Objective: To assess the risk for preeclampsia (PE) by maternal characteristics, serum placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1)at 30-33 weeks' gestation. Methods: This was a screening study in singleton pregnancies including 2,140 that subsequently developed PE and 83,615 that were unaffected by PE, gestational hypertension or delivery of small-for-gestational-age neonates (normal group). We developed a survival time model for the time of delivery for PE by combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 29 publications
4
53
0
2
Order By: Relevance
“…The following steps were carried out in our previous studies [14,15]: firstly, the values of uterine artery PI, MAP and serum PlGF and sFlt-1 were log 10 transformed to make their distribution gaussian, secondly, backward stepwise multiple regression analysis was used to determine which of the factors amongst the maternal characteristics and gestation were significant predictors of the log 10 artery PI, log 10 MAP, log 10 PlGF and log 10 sFlt-1, adjusting for the adverse pregnancy outcomes as specified (PE, GH and SGA), thirdly, the distribution of markers was expressed as multiple of median (MoM) in all cases, correcting for the significant predictors as defined in the multiple regression and fourthly, in the cases of PE regression analysis was used to determine the relationship between log 10 MoM values with gestational age at delivery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following steps were carried out in our previous studies [14,15]: firstly, the values of uterine artery PI, MAP and serum PlGF and sFlt-1 were log 10 transformed to make their distribution gaussian, secondly, backward stepwise multiple regression analysis was used to determine which of the factors amongst the maternal characteristics and gestation were significant predictors of the log 10 artery PI, log 10 MAP, log 10 PlGF and log 10 sFlt-1, adjusting for the adverse pregnancy outcomes as specified (PE, GH and SGA), thirdly, the distribution of markers was expressed as multiple of median (MoM) in all cases, correcting for the significant predictors as defined in the multiple regression and fourthly, in the cases of PE regression analysis was used to determine the relationship between log 10 MoM values with gestational age at delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Bayes' theorem was used to combine the prior information from maternal characteristics with uterine artery PI, MAP and serum PlGF and sFlt-1MoM values [13,14,15,22]. The distribution of gestational age at delivery with PE was defined by two components: firstly, the prior distribution based on maternal characteristics and secondly, the distribution of uterine artery PI, MAP and serum PlGF and sFlt-1 MoM values with gestational age in pregnancies affected by PE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that recording maternal characteristics and measuring uterine artery PI and MAP at 30-33 weeks can identify, at FPR of 5%, about 90% of cases developing PE and requiring delivery within the subsequent 4 weeks, but less than half of PE developing after this interval. These findings imply that the performance of screening requires further improvement and this is likely to be achieved by firstly, the addition of biochemical markers, such as placental growth factor and soluble fms-like tyrosine kinase-1 [33,34], and secondly, the introduction of a further integrated clinic at 36-38 weeks' gestation. Ultimately, the value of such clinics in improving perinatal outcome would need to be investigated by randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of PLGF are also reduced in the second and third trimesters of pregnancies that develop PE or deliver SGA neonates. 7,[13][14][15][16][17][18][19][20][21][22][23] While the pathophysiology of preeclampsia is not yet fully understood, there is growing evidence associating angiogenic proteins in screening, diagnosing and predicting the clinical course of the condition. 8,10,24,25 Placental growth factor (PLGF) is a proangiogenic marker that circulates at high concentrations in normal pregnancies.…”
Section: Introductionmentioning
confidence: 99%